1997
DOI: 10.1079/bjn19970156
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of total body water from bioelectrical impedance in patients with anorexia nervosa

Abstract: Total body water (TBW) was measured by deuterium oxide (DzO) dilution and predicted from bioelectrical impedance (Z) gave a more accurate prediction of TBW by bioelectrical impedance analysis on the study subjects, with biases of -0.1 (SD 1.8) and 0.5 (SD 1.7) litres in controls and patients respectively (NS). However, the individual bias was sometimes high. It is concluded that bioelectrical impedance analysis can be used to predict TBW in anorexic women at a population level, but the predictions are less g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…Besides the larger number of subjects, it is likely that the greater interindividual variability in TBW : Wt observed in the present study has contributed to this result (Scalfi et al, 1997). Not unexpectedly , the RMSE% associated with the cross-validation of the ECW equation was higher than that associated with the TBW equation (8 vs 5%).…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Besides the larger number of subjects, it is likely that the greater interindividual variability in TBW : Wt observed in the present study has contributed to this result (Scalfi et al, 1997). Not unexpectedly , the RMSE% associated with the cross-validation of the ECW equation was higher than that associated with the TBW equation (8 vs 5%).…”
Section: Discussionmentioning
confidence: 45%
“…We have the policy of systematically testing this hypothesis in our BIA studies. For instance, we have not been able to show that four-polar BIA at 50 kHz is more accurate than Wt in estimating TBW and appendicular body composition in anorexic women (Scalfi et al, 1997;Bedogni et al, 2003b). Even if the use of multifrequency instruments may change this evidence, the use of an impedance-meter is clearly not justified in these circumstances.…”
Section: Discussionmentioning
confidence: 73%
“…In homogeneous samples such as those studied here, Wt is generally a better predictor of TBW and FFM than Rl, while the contrary happens for heterogeneous samples (Kushner et al, 1992;Scalfi et al, 1997). The reason why Wt did contribute to the unexplained variance of FFM in anorexics but not in controls is unclear but it is possible that a frequency of 50 kHz may not be enough to obtain an accurate estimate of FFM in anorexics because of changes in their ECW: ICW ratio.…”
Section: Discussionmentioning
confidence: 54%
“…BIA offers accurate estimates of total body composition in anorexics, but its accuracy for the assessment of appendicular body composition in these subjects is not known (Hannan et al, 1990;Scalfi et al, 1993Scalfi et al, , 1997Polito et al, 1998). In the present study, population-specific equations were needed to obtain accurate estimates of total and appendicular FFM from BIA in anorexics.…”
Section: Discussionmentioning
confidence: 99%
“…It functions as a structural component, a medium for chemical reactions and a vehicle for interchange between the body cells and organs. It has been suggested that body water as percent of body weight increases in anorexia (Dempsey et al, 1984;Scal® et al, 1997), and it has been found to be irregularly distributed with expansion of the extracellular compartment at the expense of the intracellular (Veisman et al, 1988;Scal® et al, 1993). To estimate total body water we have used the Kushner's equation (1992) that has been validated also in anorexic patients (Scal® et al, 1997).…”
Section: Discussionmentioning
confidence: 99%